A New Modular Nail Spanning System for Cement Spacer Reconstructions after Tumor Resection of the Knee - Ephrem Phil Villaruel; Karla Teresa Araneta; Seth Arsel Escanillas; Czar Louie Gaston (Philippine Journal of Orthopaedics)
Limb Salvage procedure is now the management of choice for most musculoskeletal malignant tumors. Thanks to advances in imaging and adjuvant modalities, limb salvage has become an oncologically safe option.